2004
DOI: 10.1007/bf03346266
|View full text |Cite
|
Sign up to set email alerts
|

New paradigms in neuroendocrinology: Relationships between obesity, systemic inflammation and the neuroendocrine system

Abstract: Obesity may be an independent risk factor for coronary artery disease and contribute to a chronic state of systemic inflammation leading to atherosclerosis and metabolic abnormalities, such as diabetes, insulin resistance, dyslipidemia and hypertension. Visceral fat, in fact, may act as an endocrine organ, synthesizing and releasing atherogenic inflammatory cytokines, whose circulating levels depend on the individual's nutritional state, and the extent and anatomical location of fat stores. Unsuspected viral i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1
2

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 38 publications
2
34
1
2
Order By: Relevance
“…In this way, others studies in male Sprague-Dawley rats (71) and mice (1) have shown decreases of serum TNFm levels and fat deposition after the supplementation of 1.0-1.5% of CLA. However, feeding CLA to C57BL/6J female mice resulted in increases of TNFm tuRNA level in white adipose tissue, but decreases in skeletal muscle gene expression (57). These studies suggest that CLA may differentially affect the concentrations of TNF-~x in the serum and adipose tissue.…”
Section: Cla and Inflammatory Diseasesmentioning
confidence: 67%
“…In this way, others studies in male Sprague-Dawley rats (71) and mice (1) have shown decreases of serum TNFm levels and fat deposition after the supplementation of 1.0-1.5% of CLA. However, feeding CLA to C57BL/6J female mice resulted in increases of TNFm tuRNA level in white adipose tissue, but decreases in skeletal muscle gene expression (57). These studies suggest that CLA may differentially affect the concentrations of TNF-~x in the serum and adipose tissue.…”
Section: Cla and Inflammatory Diseasesmentioning
confidence: 67%
“…At the basic level, obesity is always due to greater energy intake than is expended, but the interaction of genetic and environmental factors that regulate both accumulation and distribution of body fat is complex. Recent studies of twins from our cohort, 2 and others, 3,4 have shown that total and central fat mass are responsible for most of the additional circulating inflammatory markers and cytokines that lead to increased heart disease. Determinants of fat accumulation include basal and sleeping metabolic rate, thermogenesis and the thermic effect of food, physical activity, efficiency of nutrient absorption by the gut and hormonal status, 5 which are all regulated differently depending on genetic make-up.…”
Section: Introductionmentioning
confidence: 63%
“…The metabolites of estrogens could be one such factor, because the 2-methyloxy-estradiol has been shown to have a destructive effect in thyroid cells cultures [22]. Infection's cytokines which are released by visceral fat have been proven to inhibit the hypothalamic-pituitary axis [23]. This will lead to negative correlations between BMI and serum TSH and between BMI and serum T4.…”
Section: Discussionmentioning
confidence: 99%